Diagnóstico sobre la aplicación de las medidas para seguridad humana y protección contra incendios en el diseño y construcción de centros comerciales - Araya-Dittel, Aitziber (Instituto Tecnológico de Costa Rica, 2010)
The measures of the human security and the protection against fire constitute elements of great transcendency inside the development of all construction projects that is sought to inhabit or to occupy. For that reason a great concern arises for the lack of knowledge among the professionals linked with this type of projects, when implementing erroneously or not to implement these measures completely. With base in that pointed out, the present project identifies the differences concerning what type of normative it should be applied or which he/she has priority and which not, around the construction of commercial centers. The nonfulfillments registered in the rejections of steps of Visa of planes show that the most vulnerable area to fire in a commercial center led to a diagnosis of the omissions in human security and protection against fires that present certain commercial centers of the Great Metropolitan Area. With support in that joint, it was determined that the main reasons of rejection in the Visa of planes in engineering of Firemen, it is the degree of the professionals' ignorance linked in construction. Before this panoramic, proposals of improvement were captured to correct this lacks and to obtain prepared better professionals as for the requested requirements, with the purpose of protecting the human life in the construction projects.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción). Instituto Tecnológico de Costa Rica. Escuela de Ingeniería en Construcción, 2010.
Keywords: Sistemas de señalización; Evacuación; Emergencia; Detectores de humo; Hidrantes; Medidas de protección